A return to ad libitum feeding following caloric restriction promotes hepatic steatosis in hyperphagic OLETF rats - Linden, Melissa A. (Am J Physiol Gastrointest Liver Physiol, 2016)
Hyperphagic Otsuka Long-Evans Tokushima fatty (OLETF) rats develop obesity, insulin resistance, and nonalcoholic fatty liver disease (NAFLD), but lifestyle modifications, such as caloric restriction (CR), can prevent these conditions. We sought to determine if prior CR had protective effects on metabolic health and NAFLD development following a 4-wk return to ad libitum (AL) feeding. Four-week-old male OLETF rats (n = 8–10/group) were fed AL for 16 wk (O-AL), CR for 16 wk (O-CR; ∼70% kcal of O-AL), or CR for 12 wk followed by 4 wk of AL feeding (O-AL4wk). CR-induced benefit in prevention of NAFLD, including reduced hepatic steatosis, inflammation, and markers of Kupffer cell activation/number, was largely lost in AL4wk rats. These findings occurred in conjunction with a partial loss of CR-induced beneficial effects on obesity and serum triglycerides in O-AL4wk rats, but in the absence of changes in serum glucose or insulin. CR-induced increases in hepatic mitochondrial respiration remained significantly elevated (P < 0.01) in O-AL4wk compared with O-AL rats, while mitochondrial [1-(14)C]palmitate oxidation, citrate synthase activity, and β-hydroxyacyl-CoA dehydrogenase activity did not differ among OLETF groups. NAFLD development in O-AL4wk rats was accompanied by increases in the protein content of the de novo lipogenesis markers fatty acid synthase and stearoyl-CoA desaturase-1 and decreases in phosphorylated acetyl-CoA carboxylase (pACC)/ACC compared with O-CR rats (P < 0.05 for each). The beneficial effects of chronic CR on NAFLD development were largely lost with 4 wk of AL feeding in the hyperphagic OLETF rat, highlighting the importance of maintaining energy balance in the prevention of NAFLD.